Decline in the Incidence of Chronic Subdural Hematoma During the Coronavirus Disease 2019 Pandemic: A Retrospective Single-Center Descriptive Study - Maeoka, Ryosuke; Nakagawa, Ichiro; Saeki, Keigo; Nakase, Hiroyuki; Ohnishi, Hideyuki (Frontiers in Neurology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has forced restrictions on social activities in some areas. There has also been a decrease in the number of trauma patients in the United States during the COVID-19 pandemic. Chronic subdural hematoma (CSDH) is a traumatic disorder that often develops following head injury. We therefore investigated the impact of the COVID-19 pandemic on CSDH. In this retrospective single-center descriptive study from April 2018 through September 2021, there were 5,282 head trauma patients and 196 patients with CSDH in the pre-pandemic group compared to 4,459 head trauma patients and 140 patients with CSDH in the intra-pandemic group. Significant decreases in the incidence rate (IR) of head trauma (951/100,000 vs. 795/100,000 person-years; IR ratio (IRR): 0.836, 95% confidence interval (CI): 0.803–0.870, p < 0.001) and also in the IR of CSDH (35.0/100,000 vs. 24.8/100,000 person-years, IRR: 0.708, 95% CI: 0.570–0.879, p = 0.002) were seen in the intra-pandemic group compared to the pre-pandemic group. In this study, the COVID-19 pandemic was associated with significant decreases in the IRs of head trauma and CSDH due to forced restrictions on social activities. Besides, the IR of mild cases of CSDH was significantly lower in the intra-pandemic group than in the pre-pandemic group (IRR: 0.68, 95% CI: 0.51–0.89, p = 0.006). Fewer people being out in communities should result in fewer chances for head trauma and CSDH. On the other hand, forced restrictions on social activities due to the COVID-19 pandemic should aggravate CSDH.